Analysis of volatile organic compounds released from SW480 colorectal cancer cells and the blood of tumor-bearing mice - Liu, Desheng; Ji, Linlin; Li, Mingjuan; Li, Dandan; Guo, Lei; Nie, Maomao; Wang, Dongchun; Lv, Yang; Bai, Yang; Liu, Miao; Wang, Guiyue; Li, Yuhang; et al. (Translational Cancer Research; Vol 8, No 8 (December 31, 2019): Translational Cancer Research, 2019)
Background: Volatile organic compound (VOC) analysis provides an elegant approach for colorectal cancer screening. An organic compound with a high vapor pressure or volatility can be detected in the headspace of cancer cells or blood samples. Therefore, analyzing VOCs in the blood of rats inoculated with colorectal cancer tissue and in SW480 medium from cultured colorectal cancer cells may provide accurate results. Methods: After collecting venous blood from rats inoculated with cancer cells at different times, the cancer tissue was removed from the inoculated rats, and the medium was harvested from the cancer cells and cultured in the presence or absence of a chemotherapy drug of intestinal epithelial cells. We used solid-phase microextraction-gas chromatography-mass spectrometry (SPME-GC-MS) to analyze the headspace of the blood and media to evaluate the VOC profiles. Statistical analysis was conducted using principal component analysis (PCA) and orthogonal partial least-squares analysis (OP-LSDA). Results: The in vivo and in vitro analyses of the colorectal cancer samples revealed a variety of compounds, such as cyclohexanone, 1-hexanol, 2-ethyl-, butylated hydroxytoluene, cyclotrisiloxane, hexamethyl-, pentanoic acid, 2,2,4-trimethyl-3-hydroxy-isobutyl ester and acetone. Butylated hydroxytoluene is unique with regard to its presence during tumor growth and resection; it is also present during tumor cell growth and necrosis. Acetone showed unique trends in the in vivo experimental group. Conclusions: By analyzing VOC fingerprints related to colorectal cancer (CRC), we found that butylated hydroxytoluene and acetone have unique signatures that may provide the basis for clinical diagnosis and disease assessment.